Niekonwencjonalna walka ze stresem – konteksty i kulturowe uwarunkowania - Judzińska, Aneta (Wydawnictwo Naukowe UAM, 2015)
The article seeks to investigate the contemporary, unconventional strategy of dealing with stress in Poland. Moreover, it represents the quintessence of various widespread tendencies of eliminating stress factors. The author examines specific remedial methods by its qualification according to the degree of conventionality and the influence on the health status. The study is extended by a sociocultural aspect which implies the culture of adrenalin and risk.
Unconventional Battle with Stress – Contexts and Cultural Determinants
Keywords: stress; ways of dealing with stress; unconventional strategies; risk culture